Diabetes Dyslipidemia. Issue 2 (June 2016) - Schofield, Jonathan; Liu, Yifen; Rao-Balakrishna, Prasanna; Malik, Rayaz; Soran, Handrean
Abstract Diabetes mellitus is associated with a considerably increased risk of premature atherosclerotic cardiovascular disease. Intensive glycemic control has essentially failed to significantly improve cardiovascular outcomes in clinical trials. Dyslipidemia is common in diabetes and there is strong evidence that cholesterol lowering improves cardiovascular outcomes, even in patients with apparently unremarkable lipid profiles. Here, the authors review the pathophysiology and implications of the alterations in lipoproteins observed in both type 1 and type 2 diabetes, the effect of medications commonly used in the management of diabetes on the lipid profile, the evidence for lifestyle and pharmaceutical interventions, and national and international recommendations for the management of dyslipidemia in patients with diabetes.